Pengaruh Dimensi Kepribadian terhadap Kinerja Karyawan dengan Pelatihan sebagai Variabel Mediasi Studi pada PT Gresik Cipta Sejahtera - Arief Tri Wicaksono; Jun Surjanti (Universitas Negeri Surabaya, 2018)
This research aimed to analyze the influence of personality dimensions on the performance of employees with training as a mediating variable. The sample used in this study were 45 marketing employees of PT Gresik Cipta Sejahtera. Statistical method analyze technique used is Structural Equation Model Partial Least Square by using Smart PLS 2.0. The results of recent research showed that the dimension of personality extraversion, agreeableness, neuroticsm, openness had significant positive effect on performance, Dimensions of Personality conscientinouness had a negative effect and significant to the performance. Dimensions of personality extraversion conscientinouness, openness had positive effect and significant to training, dimensions of personality agreeableness, neuroticsm had positive effect but not significant to training, training had positive and significant impact on performance.Training did not mediate the effect between Dimensions of Personality extraversion, agreeableness, neuroticsm, openness on performance, training did mediate the effect between Dimensions of Personality conscientinouness on performance.